DIAGNOSTICS AND TREATMENT OF THE SEPSIS AND SEPTIC SHOCK IN CHILDREN - R.F. Tepaev (Union of pediatricians of Russia, 2010)
Sepsis is one of the leading causes of mortality in children. Timely diagnosis is the most important condition of successful therapy for sepsis. The work provides modern recommendations for diagnosis of the systemic inflammatory response syndrome, sepsis, severe sepsis, septic shock, sets out key guidelines for administering and treating severe sepsis and septic shock in children. Key words: systemic inflammatory response syndrome, sepsis, septic shock, children. (Pediatric Pharmacology. - 2010; 7(5):24-29)